Endotoxin Activity in Patients With Extracorporeal Membrane Oxygenation Life Support: An Observational Pilot Study - Lee, Chen-Tse; Wang, Chih-Hsien; Chan, Wing-Sum; Tsai, Yun-Yi; Wei, Tzu-Jung; Lai, Chien-Heng; Wang, Ming-Jiuh; Chen, Yih-Sharng; Yeh, Yu-Chang (Frontiers in Medicine, 2021)
Background: Extracorporeal membrane oxygenation (ECMO) life support has become an integral part of intensive care. The endotoxin activity assay (EAA) is a useful test to measure endotoxemia severity in whole blood. To date, no information is available regarding the EAA levels and their effect on clinical outcomes in critically ill patients with ECMO support. Methods: This prospective observational pilot study enrolled adult critically ill patients with ECMO support from August 2019 to December 2020. The EAA levels were measured within 24 hours (T1), and at 25–48 (T2), 49–72 (T3), and 73–96 hours (T4) after ECMO initiation. This study primarily aimed to investigate the incidence of high EAA levels (≥0.6) at each time point. Subsequent exploratory analyses were conducted to compare the EAA levels of venoarterial ECMO (VA-ECMO) patients between 30-day survivors and nonsurvivors. Post hoc analysis was performed to compare the clinical outcomes of VA-ECMO patients with elevated EAA levels at T3 (vs. T1) and those without elevated EAA levels. Results: A total of 39 VA-ECMO patients and 15 venovenous ECMO (VV-ECMO) patients were enrolled. At T1, the incidence of high EAA level (≥0.6) was 42% in VV-ECMO patients and 9% in VA-ECMO patients (P = 0.02). At T2, the incidence of high EAA level was 40% in VV-ECMO patients and 5% in VA-ECMO patients (P = 0.005). In VA-ECMO patients, EAA levels at T3 were significantly higher in 30-day nonsurvivors than in survivors (median [interquartile range]: 0.49 [0.37 to 0.93] vs. 0.31 [0.19 to 0.51], median difference 0.16 [95% confidence interval [CI], 0.02 to 0.31]; P = 0.024). Moreover, VA-ECMO patients with elevated EAA levels at T3 (vs. T1) had lower 30-day survival than patients without elevated EAA levels had (39% vs. 83%, P = 0.026) and fewer ECMO free days by day 30 (median: 3 vs. 23 days, median difference 12 days [95% CI, 0 to 22]; P = 0.028). Conclusions: A certain proportion of patients experienced high EAA levels (≥0.6) after VV-ECMO or VA-ECMO initiation. VA-ECMO patients with an elevated EAA level at 49–72 hours were associated with poor clinical outcomes.